Design and Regulatory Institutionality in Argentine Law - Muratorio, Jorge Ignacio (2015)
The present article describe us an overview of regulatory law, his function and thecharacteristics that it should present to achieve the goal of improve some relevant economic activities for the needs of the society. After that, the author will describe us the present situation of regulation on Argentinian law.